Emotional competence and bullying - Sánchez, Virginia; Ortega, Rosario; Menesini, Ersilia (Anales de Psicología / Annals of Psychology, 2012)
In the last years, the studies on bullying are underlining the need to study the emotional and moral dimension of children involved in bullying in order to explain the origin and development of this phenomenon. The present theoretical study will analyze these dimensions following the model of Emotional Competence developed by Carolyin Saarni (1999). This functionalist and contextual approach allows investigating the emotional abilities of the person in relation to the way we are able to initiate and maintain symmetrical and satisfactory interpersonal relationships. In particular three groups of emotional skills of victims and bullies are revised: the emotional attribution, the moral dimension of the emotional experience and, the emotion regulation skills. Taking into account the most relevant results of the studies, this work concludes about the difficulties that bullies present in socio-moral tasks, meanwhile victims present prob- lems in emotion regulation and coping strategies. Key elements for direct intervention programs with bullies and victims are addressed.